Efficacy and safety of D. pteronyssinus immunotherapy in local allergic rhinitis: a double‐blind placebo‐controlled clinical trial. Issue 7 (13th April 2016) - Rondón, C.; Campo, P.; Salas, M.; Aranda, A.; Molina, A.; González, M.; Galindo, L.; Mayorga, C.; Torres, M. J.; Blanca, M.
Abstract: The effects of allergen immunotherapy (AIT) on local allergic rhinitis (LAR) are largely unknown. We conducted the first randomized, double‐blind, placebo‐controlled (DBPC), phase II trial of D. pteronyssinus (DP) subcutaneous AIT (DP‐AIT) on LAR (clinicaltrials.gov identifier: NCT02123316). Thirty‐six LAR patients received Pangramin PLUS DP or placebo for 24 months. The primary endpoints were symptoms, medication scores, and medication‐free days. The secondary included skin test, serum specific IgE and IgG4, nasal allergen provocation test (NAPT), and adverse events. AIT‐DP produced significant improvements in both primary and secondary endpoints vs placebo. After 12 months of AIT‐DP, we detected a significant and marked increase in allergen tolerance with negative NAPT in 50% of patients, and significant increases of serum sIgG4. Immunotherapy was well tolerated; no systemic reactions were reported. This study demonstrated that AIT‐DP is a safe and clinically effective treatment for LAR, confirming that LAR is a new indication for AIT.